The relationship between nutritional status and incidences of iron deficiency anemia in 3rd-trimester pregnant women in the co-endemic areas of Bengkulu City, Indonesia - Rostika Flora; Nova Nurliza; Rico Januar Sitorus; Muhammad Zulkarnain; Achmad Fickry Faisya; Samwilson Slamet (AOSIS, 2019)
Iron deficiency in pregnant women can lead to premature birth and LBW babies. This study aimed to determine the relationship between nutritional status and the incidence of Iron Deficiency Anemia in the 3rd trimester pregnant women in the co-endemic area of Bengkulu City. This study was a cross-sectional study with a total sample of 108 respondents who met the inclusion criteria. The sampling technique was carried out by purposive sampling. Data obtained through interviews and questionnaires. Data was analyzed by using chi-square test and multiple logistic regressions. The results showed that pregnant women who had <23.5 cm of MUACwere 30.6% and 22.2% and mothers experienced Iron Deficiency Anemia were 22.2%. There was a significant relationship (p<0.05) between nutritional status and the incidence of Iron Deficiency Anemia in pregnant women. Educational factor was the most influential factor that influence the incidence of Iron Deficiency Anemia (OR = 10.303, 95% CI 2.95-35.89). It can be concluded that pregnant women with poor nutritional status have the opportunity to experience Iron Deficiency Anemia.